Pengaruh Pemberian Teripang (Stichopus horrens) terhadap Penurunan Berat Badan Siswa-Siswi SMK Bintan Insani Tanjungpinang - Sartika, Lili; Yanti, Masyitah Novia; Rahardiantini, Ikha; Trianingsih, Ayu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Excessive body fat accumulation leading to obesity can result from an imbalance between energy intake and expenditure. The body's physiological mechanisms, which are influenced by nutrient intake, play a crucial role in maintaining body weight stability. Sea cucumber (Stichopus horrens), a marine natural resource, is a potential source of nutrition. This study evaluates the effect of sea cucumber administration on weight loss in obese respondents. A true experimental design with total sampling technique was used. Statistical analysis was performed using the Wilcoxon test with the help of SPSS software version 22. The results indicate a significant weight loss in respondents after receiving treatment, with a ρ value of 0.000.